Collaborating to deliver value in health care: exploring conditions required for successful healthcare and life science sector collaboration. Issue 1 (10th August 2020) - Rees, Daniel J.; Bates, Victoria; Thomas, Roderick A.; Brooks, Simon B.; Laing, Hamish; Davies, Gareth H.; Williams, Michael; Phillips, Leighton; Dwivedi, Yogesh K.
Abstract : Purpose: The UK Government-funded National Health Service (NHS) is experiencing significant pressures because of the complexity of challenges to, and demands of, health-care provision. This situation has driven government policy level support for transformational change initiatives, such as value-based health care (VBHC), through closer alignment and collaboration across the health-care system-life science sector nexus. The purpose of this paper is to evaluate the necessary antecedents to collaboration in VBHC through a critical exploration of the existing literature, with a view to establishing the foundations for further development of policy, practice and theory in this field. Design/methodology/approach: A literature review was conducted via searches on Scopus and Google Scholar between 2009 and 2019 for peer-reviewed articles containing keywords and phrases "Value-based healthcare industry" and "healthcare industry collaboration". Refinement of the results led to the identification of "guiding conditions" (GCs) for collaboration in VBHC. Findings: Five literature-derived GCs were identified as necessary for the successful implementation of initiatives such as VBHC through system-sector collaboration. These are: a multi-disciplinarity; use of appropriate technological infrastructure; capturing meaningful metrics; understanding the total cycle-of-care; and financial flexibility. This paper outlines research opportunities to empirically test the relevance of the five GCs with regard to improving system-sector collaboration on VBHC. Originality/value: This paper has developed a practical and constructive framework that has the potential to inform both policy and further theoretical development on collaboration in VBHC.